(untitled) (Journal of Philosophy Culture and Political Science, 2021)
This article examines the issues of determining the place and role of science in the formation of the worldview picture of the world from antiquity to the present day. The author comes to the conclusion that the problems and principles underlying the determination of the philosophical and methodological authenticity and reliability of knowledge in the ancient, medieval, and also in the modern European environment, were in a state of permanent confrontation between science and nonscience, demonstrating not so much polemics of opposing views on the prevalence of a grounded or imagined worldview, how many philosophers’ views on the very essence of knowledge, which later, after enlightenment transformations, nevertheless took shape in skepticism and materialistic denial of everything unreasonable, unprovable. Litigation to Determine the Criteria of Genuine Knowledge in the 20th Century served as a reason for the emergence of logical relativism, however, by our time, the dispute has not been resolved and in the modern dispute about scientific and unscientific knowledge, the condemnation of metaphysics and theories about the interpenetration of available knowledge with other ways of knowing the world is gaining increasing recognition. The article reveals the features of the search and argumentation of knowledge, which were used by leading historical personalities. The author, through an analysis of the work of famous scientists from antiquity to our time, reveals the principles and methods underlying the definition of the boundaries of knowledge. It is noted that in modern philosophy this issue is not completely resolved, but there are a number of interesting assumptions about reliable and unreliable knowledge and the criteria for its determination. Keywords: science, metaphysics, authenticity of knowledge, credible science, grounded knowledge, evidence-based science, logical relativism, demarcation